Herd health innovations improve pig farmers’ knowledge and uptake of husbandry practices in Uganda - Oba, Peter; Businge, Martha; Hasahya, Emmanuel; Dione, Michel M.; Kawuma, Peter; Wairagala, Pamela; Bamundaga, Geoffrey; Ahumuza, Ronnie; Kaweesa, Peter; Namatovu, Jane; Kalenzi, Moses S.; Achandi, Esther L.; et al. (International Livestock Research Institute, 2024)
In Uganda, pigs play an important role in the livelihoods of farmers, contributing significantly to both food security and income generation. However, the value chain faces many challenges which range from diseases, inadequate access to production inputs, information and knowledge gaps (Dione et al., 2014, Oba et al., 2023). These contribute to poor herd performance, low productivity and inability to access better marketing opportunities (Ouma et al., 2016). To overcome these challenges, the International Livestock Research Institute (ILRI) designed and implemented a CGIAR initiative “Sustainable Animal Productivity for Livelihoods, Nutrition and Gender inclusion” (SAPLING). SAPLING’s primary objective is to improve pig productivity, incomes and empower pig farmers (women, men, and youth) in pig production and value chain actors involved in pig related businesses in Uganda. This initiative was implemented in Uganda by ILRI, working closely with its national partners, the Ministry of Agriculture, Animal Industry and Fisheries (MAAIF), the district local governments in Uganda's central region (Masaka, Mpigi, Mukono and Wakiso) and selected pig farmer groups.